2014
DOI: 10.2174/0929867321666140826120844
|View full text |Cite
|
Sign up to set email alerts
|

Thyroglobulin Autoantibodies as Surrogate Biomarkers in the Management of Patients with Differentiated Thyroid Carcinoma

Abstract: Differentiated thyroid cancer is a rare malignancy, but leaves numerous survivors for life-long follow-up. The cornerstone in current guidelines for follow-up is by measuring the thyroid specific tumour marker, thyroglobulin in serum. Most patients can be followed by this method, but some thyroid cancer patients have antithyroglobulin antibodies in serum, both at diagnosis and after treatment, where follow-up is commenced. These antibodies interfere technically in the immunological methods for measuring thyrog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…Previous studies have shown that higher titers of anti-Tg antibodies are associated with higher risk of recurrence and have found that the higher the levels of these antibodies, the higher the chances of tumor recurrence (50)(51)(52). Although the presence of antibodies hinders the use of Tg as a followup marker, in some cases the serial TgAb measurements function as a surrogate marker (53). Thus, the majority of patients with DTC and positive TgAb tend to exhibit a progressive decline in titers of these antibodies, and a new increase in antibody levels may be considered a sign of tumor recurrence (52,53).…”
Section: Tg Heterogeneity: Clinical Applications and Future Perspectivesmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have shown that higher titers of anti-Tg antibodies are associated with higher risk of recurrence and have found that the higher the levels of these antibodies, the higher the chances of tumor recurrence (50)(51)(52). Although the presence of antibodies hinders the use of Tg as a followup marker, in some cases the serial TgAb measurements function as a surrogate marker (53). Thus, the majority of patients with DTC and positive TgAb tend to exhibit a progressive decline in titers of these antibodies, and a new increase in antibody levels may be considered a sign of tumor recurrence (52,53).…”
Section: Tg Heterogeneity: Clinical Applications and Future Perspectivesmentioning
confidence: 99%
“…Although the presence of antibodies hinders the use of Tg as a followup marker, in some cases the serial TgAb measurements function as a surrogate marker (53). Thus, the majority of patients with DTC and positive TgAb tend to exhibit a progressive decline in titers of these antibodies, and a new increase in antibody levels may be considered a sign of tumor recurrence (52,53). However, anti-Tg antibody positivity itself does not correlate directly with worse prognosis, unless titers increase progressively.…”
Section: Tg Heterogeneity: Clinical Applications and Future Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…For TgAb-positive patients, the use of serum levels of TgAb as a 'surrogate tumor marker' has been widely adopted in clinical practice (i.e. declining TgAb levels may indicate reduced tumor burden or the absence of disease while the persistence of anti-Tg antibodies, especially if levels are rising, may indicate persistent, recurrent or progressive thyroid cancer) (1,3,4,11). However, the serum levels of TgAbs are not correlated with the tumor load of the patient, but rather indicate the activity of the immune system.…”
Section: Introductionmentioning
confidence: 99%
“…In an attempt to elucidate if the presence of TPO.Ab in breast cancer was an expression of a generalised immune response to the cancer or a true indication of autoimmune thyroid disease the author explored the relevance as to the significance of detectable rather than elevated levels of TPO.Ab in breast cancer [15,16]. Examining serum TPO.Ab concentration and its relationship to TSH in patients with postmenopausal breast cancer compared to postmenopausal controls it emerged that there was an association, not only between elevated TPO.Ab (>20.0 kIU/l) and serum TSH but that this association also applied to those patients with breast cancer who had detectable TPOAb (>2.0 < 20.0 kIU/l).…”
mentioning
confidence: 99%